Bound states and glueballs in three-dimensional Ising systems - Caselle, M.; Hasenbusch, Martin; Provero, P.; Zarembo, K. (Nuclear physics. B, Particle physics, 2002)
We study the spectrum of massive excitations in three-dimensional models belonging to the Ising universality class. By solving the Bethe-Salpeter equation for 3D φ4 theory in the broken symmetry phase we show that recently found non-perturbative states can be interpreted as bound states of the fundamental excitation. We show that duality predicts an exact correspondence between the spectra of the Ising model in the broken symmetry phase and of the Z2 gauge theory in the confining phase. The interpretation of the glueball states of the gauge theory as bound states of the dual spin system allows us to explain the qualitative features of the glueball spectrum, in particular, its peculiar angular momentum dependence.
Gesehen am 05.07.2022